Design and development of a high-density, high-speed 10 kV SiC MOSFET module - Di Marino, Christina; Boroyevich, Dushan; Burgos, Rolando; Johnson, Christopher Mark; Lu, G.-Q. (2017)
High-density packaging of fast-switching power semiconductors typically requires low parasitic inductance, high heat extraction, and high thermo-mechanical reliability. High-density packaging of high-voltage power semiconductors, such as 10 kV SiC MOSFETs, also requires low electric field concentration in order to prevent premature dielectric breakdown. Consequently, in addition to the usual electromagnetic, thermal, and mechanical analyses, the electric fields must also be evaluated. This is the first detailed report on the optimization of a high-voltage SiC MOSFET power module.